Protected citrus nursery production is a profitable enterprise - Thakur, Anirudh; Dhaliwal, HS; Kashyap, Poonam (Indian Horticulture, 2019)
The sustainable enhancement in fruit production can be achieved by supplying genuine, healthy and high-quality planting material of recommended varieties to farmers. The persistent threat of spread of bud transmissible diseases and root rot with nursery plants makes production of citrus nursery a highly specialized and technical job. Techniques like direct sowing, bud forcing and urea sprays under protected nursery conditions can reduce the multiplication time of fruit crops like citrus from 2-2Â½ years in traditional citrus nurseries to 1-1Â½ years in protected nursery. Smaller nursery area is required for containerized nursery production and there is no need to change nursery sites every year. A module has been developed for the containerized nursery production of citrus plants under protected structures for fast multiplication of plants for fulfilling the ever-increasing demand for quality planting material of citrus plants.